2015
DOI: 10.1002/ceat.201500064
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Catalytic Oxidation of Sulfite in Diluted Aqueous Solutions

Abstract: The reaction kinetics for low concentrations of sulfite close to the stoichiometric ration of oxygen was investigated in a rapid-mixing apparatus. Air-or pure oxygen-saturated solution containing the catalyst was mixed with aqueous sulfite solution. Mixing ratios with stoichiometric excess of dissolved oxygen were tested. Reaction orders for sulfite, oxygen, and a Co(II) catalyst from literature were confirmed in the tested concentration range. The apparent kinetic constant and activation energy data are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Reactions to form radical species are as follows (similar reactions can also be written for HSO 3 − ): This reaction sequence is a known important in-cloud sulfate formation pathway. …”
Section: Introductionmentioning
confidence: 99%
“…Reactions to form radical species are as follows (similar reactions can also be written for HSO 3 − ): This reaction sequence is a known important in-cloud sulfate formation pathway. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, oxygen scavenging by sulfite compounds is an important task to inhibit corrosion in industrial water circuits. In chemical engineering and mass transfer studies the cobalt‐catalysed reaction of sulfite to sulfate has been intensively investigated [Scheme , (1)] , , , . Mostly, oxygen and its consumption is indicated by ruthenium complexes and their fluorescence abilities as mentioned above by LIF.…”
Section: Systems With O2mentioning
confidence: 99%
“…For example, it has been established that some organic acids, such as oxalic acid and formic acid, have a strong inhibition effect on iron-catalyzed S(IV) oxidation due to the complexation of organic ligands with iron. 4−6 The catalytic oxidation of S(IV) is a free-radical chain reaction, 3,7,8 where sulfoxy radicals, that is, SO 3 − , SO 4 − , and SO 5 − radicals, are the major intermediates. Therefore, besides complexation with TMI, organic compounds can also react with sulfoxy radicals, resulting in the decrease of sulfoxy radical concentration and subsequently altering the rate of catalytic S(IV) oxidation as well as the conversion of S(IV).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that this reaction can also be influenced by other reactions, in particular, in the presence of organic compounds. For example, it has been established that some organic acids, such as oxalic acid and formic acid, have a strong inhibition effect on iron-catalyzed S­(IV) oxidation due to the complexation of organic ligands with iron. The catalytic oxidation of S­(IV) is a free-radical chain reaction, ,, where sulfoxy radicals, that is, SO 3 – , SO 4 – , and SO 5 – radicals, are the major intermediates. Therefore, besides complexation with TMI, organic compounds can also react with sulfoxy radicals, resulting in the decrease of sulfoxy radical concentration and subsequently altering the rate of catalytic S­(IV) oxidation as well as the conversion of S­(IV). The three main pathways for these reactions in aqueous phase are summarized in reactions – (using SO 4 – radical as an example): , Specifically, the ·SO 4 – radical can react with saturated organic compounds through hydrogen abstraction (R1), transfer of an electron from an aromatic compound (R2), and undergo addition reactions with organic compounds containing carbon–carbon double bonds (R3).…”
Section: Introductionmentioning
confidence: 99%